Nonendemic rhinoscleroma: An unusual manifestation of the trachea - Joseph Celidonio; Rohini Bahethi; Raj Malhotra; Suchitra Sangappa; Rachel Kaye (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objectives Rhinoscleroma is classically described as a chronic granulomatous disease caused by Klebsiella rhinoscleromatis which primarily affects the nose and nasopharynx. When present, tracheal manifestations will be seen late in the disease course rather than on initial presentation. We describe a rare case of nonendemic rhinoscleroma that presented with tracheal lesions as an initial manifestation of disease. Methods Case report and literature review. Results An 88‐year‐old male presented with longstanding dysphonia. Flexible laryngoscopy demonstrated a septal perforation and diffuse glottic lesions. CT neck demonstrated a nonobstructive polypoid tracheal lesion and mucosal thickening of the paranasal sinuses. Biopsy confirmed an atypical lympho‐histiocytic proliferation and microorganisms within macrophages on Grocott methenamine silver and Steiner stains consistent with rhinoscleroma. He was referred for rheumatology and pulmonology consultation. Conclusion Systemic diseases rarely affect the trachea, and even less frequently is a tracheal lesion identified as the initial manifestation of disease. The most common systemic diseases that affect the trachea include relapsing polychondritis, granulomatosis with polyangiitis, amyloidosis, and inflammatory bowel disease. The literature surrounding nasolaryngotracheal rhinoscleroma is limited, especially in nonendemic areas. It is necessary to include unusual etiologies of airway lesions in the differential diagnosis, which warrants comprehensive airway evaluation including biopsy. Level of Evidence 4.